EFFECTIVENESS OF GABAPENTIN USAGE TOWARD REDUCING PAIN INTENSITY LEVEL AND QUALITY OF LIFE OF POST-STROKE NEUROPATHIC PATIENTS IN REGIONAL GENERAL HOSPITAL, WEST NUSA TENGGARA PROVINCE YEAR 2018 - QIYAAM, NURUL; ADIKUSUMA, WIRAWAN; NOPITASARI, BAIQ LENY; ANDAYANI, TRI MURTI; AMINI, AULIA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Stroke is defined as a sudden loss of brain function due to blockade/rupture of the brain’s blood vessels. Data collected by the Indonesian Stroke Foundation show that Indonesia ranks first in Asia as the country with the highest number of stroke sufferers. The purpose of this study was to determine the effectiveness of the use of gabapentin to reduce pain intensity and improve the quality of life of post-stroke neuropathic pain in NTB Province hospital patients. Methods: This study was carried out in the period of June–July 2018. The targeted population was all post-stroke neuropathic patients who received gabapentin therapy in NTB provincial hospital. Affordable populations are post-stroke neuropathic pain patients who seek outpatient treatment at NTB provincial hospital that meets the inclusion and exclusion criteria. The results of the data will be analyzed using paired sample t-test. Obtained 15 patients were willing to participate in this study. Results: The results of the study using questionnaire EQ-5D-3L after using gabapentin for 2 weeks. Patients experienced an improvement in the quality of life in each dimension items, namely the ability to walk/move from 6.7%, no problem to 60%, no self-care, 26.7% no problem to be 80% without problems, usual activities carried out from 13.3% had no problems to 46.7% had no problems, feeling of pain/discomfort from 60% having moderate problems to 60% had no problems, and anxiety/depression of 60% had no problem being 100% has no problem. While the measurement of the quality of life using the EQ-VAS questionnaire, there was a significant improvement in the quality of life between before and after using gabapentin at 32.66. Conclusion: The use of gabapentin has effectiveness on reduction of pain intensity and the quality of life of post-stroke neuropathic patients in regional general hospital, West Nusa Tenggara Province year 2018.